2022
DOI: 10.21203/rs.3.rs-1207364/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Omicron: evasion of potent humoral responses and resistance to clinical immunotherapeutics relative to viral variants of concern

Abstract: Genetically distinct viral variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been recorded since January 2020. Over this time global vaccine programs have been introduced, contributing to lowered COVID-19 hospitalisation and mortality rates, particularly in the first world. In late 2021, the Omicron (B.1.1.529) virus variant emerged, with significant genetic differences and clinical effects from other variants of concern (VOC). This variant a demonstrated higher number of polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…The extensive mutations in the Omicron spike gene mark a dramatic alteration in its antigenicity 15 . Omicron has high transmissibility and high level of immune evasion from WT mRNA vaccine induced immunity, which was reported from various emerging literature 6,1417 . Omicron’s strong association with reinfection 6 or breakthrough infection 8,12 and its heavily altered antigenicity prompted the idea of developing Omicron-specific mRNA vaccine.…”
Section: Discussionmentioning
confidence: 93%
“…The extensive mutations in the Omicron spike gene mark a dramatic alteration in its antigenicity 15 . Omicron has high transmissibility and high level of immune evasion from WT mRNA vaccine induced immunity, which was reported from various emerging literature 6,1417 . Omicron’s strong association with reinfection 6 or breakthrough infection 8,12 and its heavily altered antigenicity prompted the idea of developing Omicron-specific mRNA vaccine.…”
Section: Discussionmentioning
confidence: 93%
“…Researchers in Botswana and South Africa identified a new and heavily mutated SARS-CoV-2 variant (B.1.1.529, Omicron) in late November 2021, with 30 amino acid mutations in the Spike protein that are distinct compared to other variants of concern (VOC) Alpha, Beta and Delta 1 . Omicron is characterised by fastspreading in previously vaccinated populations, suggesting Omicron's ability to evade vaccine-induced immunity 2 and therapeutic monoclonal antibody therapy 3 . Several recent studies have indeed confirmed a substantial reduction in neutralising antibody activity against Omicron in small-scaled studies including previously-infected individuals, fully vaccinated individuals, recipients of third booster doses of BNT162b2 or mRNA-1273 and individuals with hybrid immunity (infection followed by vaccination) [4][5][6][7][8][9] .…”
mentioning
confidence: 99%
“…Specifically, physicians recommended sotrovimab 37 for COVID-19 treatment, as Delta was the predominant circulating strain at the time. Our assays indicated patient samples were positive for Omicron, which is resistant to monoclonal antibody treatment 38 . This allowed for physicians to pursue other treatment avenues.…”
Section: Public Health Surveillance Applicationsmentioning
confidence: 80%